eWOM dan Niat Adopsi Starlink: Studi pada Generasi Milenial di Indonesia - Christianto, Fendy; Wahab, Zakaria; Shihab, Muchsin Saggaff; Hanaﬁ, Agustina (Universitas Muhammadiyah Pontianak, 2025)
This study examines the influence of electronic word of mouth (eWOM) on the intention to adopt Starlink among Indonesian millennials, with subjective norms and perceived risk as mediators. An online survey of 340 respondents was analyzed using PLS-SEM. Results reveal that eWOM indirectly affects behavioral intention through both mediators. These findings highlight the importance of social and psychological perceptions in shaping technology adoption intention and offer strategic insights for tech companies to design effective digital communication.